Take-off velocity, force and power features manifestation in training exercises of athletes - Pyanzin, A.; Pyanzina, N. (BIO Web of Conferences, 2020)
The purpose of the study is to identify take-off velocity, force and power features manifestation in training exercises of athletes. 11 training exercises were subjected to metrological assessment. Analysis of take-off indicators allows us to assess their level individually for each athlete in each exercise. It greatly facilitates the coach`s task of individual exercises selection.